Insights Into the Older Adults' World: Concepts of Aging, Care, and Using Assistive Technology in Late Adulthood - Wiktoria Wilkowska; Julia Offermann-van Heek; Thea Laurentius; L. Cornelius Bollheimer; Martina Ziefle (Frontiers Media S.A., 2021)
The ongoing demographic change forces different stakeholders to cope with increasing needs in nursing care and the economic costs. Consequences arising from the population aging can be supported by assistive technologies to maintain older individuals' autonomy. However, older adults' opinions on the assistance of health-related technologies and their attitudes toward aging and care largely remain underexplored. This paper provides a geriatric and socio-technical perspective, investigating individual perceptions of (a) aging, (b) nursing care, and (c) the adoption of assistive technologies in a cross-national subject group. For this purpose, N = 384 individuals (60+ years) participated in an online survey. Findings indicate that most older adults are open to assistive technologies and that individual care preferences contribute to a successful adoption of these technologies. Among individual factors, health status, and gender affect respondents' opinions the most. Our findings help to understand older adults' acceptance of assistive technologies and contribute to the research on the nursing care in private and professional environments.